Exploring New Bioorthogonal Catalysts: Scaffold Diversity in Catalysis for Chemical Biology - Yan Zhang; Qizhen Huang; Fang Lei; Wanlong Qian; Chengfeng Zhang; Qi Wang; Chaoqun Liu; Haiwei Ji; Faming Wang (Advanced Science, 2025)
Abstract Bioorthogonal catalysis has revolutionized the field of chemical biology by enabling selective and controlled chemical transformations within living systems. Research has converged on the development of innovative catalyst scaffolds, seeking to broaden the scope of bioorthogonal reactions, boost their efficiency, and surpass the limitations of conventional catalysts. This review provides a comprehensive overview of the latest advancements in bioorthogonal catalyst research based on different scaffold materials. Through an in‐depth analysis of fabrication strategies and applications of bioorthogonal catalysts, this review discusses the design principles, mechanisms of action, and applications of these novel catalysts in chemical biology. Current challenges and future directions in exploring the scaffold diversity are also highlighted. The integration of diverse catalyst scaffolds offers exciting prospects for precise manipulation of biomolecules and the development of innovative therapeutic strategies in chemical biology. In addition, the review fills in the gaps in previous reviews, such as in fully summarizing the presented scaffold materials applied in bioorthogonal catalysts, emphasizing the potential impact on advancing bioorthogonal chemistry, and offering prospects for future development in this field.